GC-MS Analysis (Gas Chromatography - Mass Spectrometry) Ethanol Extract (Actinopyga echinites) on The Coast Of Puntondo Beach, District Takalar - Munisa, A. Munisa; A.Muflihunna; Hartono (Bionature, 2024)
A This research aims to determine the polar bioactive compounds contained inActinopyga echiniteswho live on Puntondo Beach, Takalar Regency. Method used for extraction Actinopyga echinitesis a wet maceration method using 96% ethanol solvent. The extract results were analyzed using gas chromatography - mass spectrometry (GC-MS) to obtain information on the internal contentActinopyga echinites. The results of GC-MS analysis from this study showed that there were 123 possible compound components that were extracted using ethanol solvent. The research results also show that there are ten possible polar bioactive compounds in the highest peak of the GC-MS analysis results, namely: trans-13- Octadecenoic acid, cis-13-Octadecenoic acid, trans-13-Octadecenoic acid, methyl ester, n-Hexane, 9- Octadecenoic acid (Z)-, oxiranylmethyl ester, Hexadecanoic acid, methyl ester, and trans-13-Octadecenoic acid. Keywords: Actinopyga echinites, GC-MS, Puntondo Beach